Kualitas Pelayanan, Kualitas Produk dan Harga Berpengaruh Terhadap Kepuasan Pelanggan di Oxyco Café Solobaru - Damar Putranto; Indra Hastuti; Esti Dwi Rahmawati (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The research entitled "Quality of Service, Product Quality and Price Influence on Customer Satisfaction at Oxyco Café Solobaru" aims to find out how customer satisfaction is influenced by the quality of service, product quality, and price. The quantitative and associative methods used in this study are double linear regression. The study of the relationship between two or more variables is considered an association. Because the population of the study is unknown, sampling was conducted using a non-opportunity method. Heir et al. method for measuring samples Research results show that customer satisfaction is significantly influenced by the quality of service, product quality, and price. In addition, service quality variables, product quality, and price are also significantly influenced by dependent variables.